Persepsi Guru BK Tentang Pelayanan Arah Peminatan Peserta Didik dalam Kurikulum 2013 - Setiawati, Mayang; Wibowo, Mungin Eddy (Indonesian Journal of Guidance and Counseling: Theory and Application, 2016)
Curriculum 2013 is a new curriculum that began piloted in Indonesia in June 2013. The main program in the curriculum of 2013 were services towards specialization of students, where students are given the opportunity to select a group of subjects according to their respective interests. Services learners toward specialization is part of the guidance and counseling program. Counselors are key actors in the service direction of specialization students. So counselors are required to have a high perception .The objective of this study were  to determine how the perceptions of high schoolâs counselor in Pekalongan on service toward specialization learners in implementation of curriculum 2013. The research was conducted in Pekalongan , with respondents counselor in high schools in Pekalongan , amounting to 23 respondents. This study was included in the survey with descriptive statistical analysis methods . This study uses only one variable that is counselor perceptions of student services towards specialization in implementation of curriculum 2013. The population of this research is the counselor in high schools in Pekalongan, and the sampling technique used was purposive sampling .